Development of interactive media for traditional music learning to foster students' critical reflection - Ilham Saputra; Indar Sabri; Welly Suryandoko; Retnayu Prasetyanti Sekti; Trisakti Trisakti; Warih Handayaningrum (Curricula: Journal of Curriculum Development, 2025)
The limited familiarity of students with local culture, especially the traditional musical instrument Thuk-thuk, and the lack of contextual interactive learning media motivated this study. The goal was to develop an interactive instructional video based on local culture to improve the critical thinking skills of eighth-grade students in Bangkalan Regency. Using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), the research combined interactive digital media, local content, and critical thinking indicators from the Paul & Elder framework. Findings revealed most students were unfamiliar with the Thuk-thuk, and suitable learning resources were rare. The video was created to meet the Merdeka Curriculum’s learning goals. Expert validation in subject matter, media, and language confirmed its high quality. Implementation in two classes showed a moderate but statistically significant improvement in students’ critical thinking skills. Besides delivering content visually and auditorily, the video encourages active engagement in analysis and evaluation while promoting the preservation of local culture. Thus, this video serves as an innovative and effective teaching tool for Cultural Arts education.   Abstrak Kurangnya pengenalan peserta didik terhadap budaya lokal, khususnya alat musik tradisional Thuk-thuk, serta terbatasnya media pembelajaran interaktif yang kontekstual menjadi latar belakang penelitian ini. Penelitian ini bertujuan mengembangkan video pembelajaran interaktif berbasis budaya lokal untuk meningkatkan kemampuan berpikir kritis peserta didik kelas VIII SMP di Kabupaten Bangkalan. Dengan menggunakan model pengembangan ADDIE (Analyze, Design, Develop, Implement, Evaluate), penelitian mengintegrasikan media digital interaktif, konten lokal, dan indikator berpikir kritis berdasarkan kerangka Paul & Elder. Hasil analisis menunjukkan sebagian besar peserta didik belum mengenal Thuk-thuk dan media pembelajaran yang ada masih sangat terbatas. Video pembelajaran dirancang sesuai capaian Kurikulum Merdeka dan divalidasi oleh ahli materi, media, serta bahasa dengan hasil sangat layak digunakan. Implementasi pada dua kelas menunjukkan peningkatan signifikan dalam kemampuan berpikir kritis peserta didik, dengan kategori sedang menurut uji statistik. Video ini tidak hanya menyampaikan materi secara visual dan auditif, tetapi juga mendorong keterlibatan aktif peserta didik dalam analisis, evaluasi, serta pelestarian budaya lokal. Dengan demikian, video ini menjadi media ajar yang inovatif, efektif, dan kontekstual untuk pembelajaran Seni Budaya. Kata Kunci: berpikir kritis; budaya lokal; Thuk-thuk; video pembelajaran interaktif